Success, innovation and challenge: School safety and disaster education in South America and the Caribbean. (April 2020) - Muñoz, Viviana Aguilar; Carby, Barbara; Abella, Enrique Castellanos; Cardona, Omar Dario; López-Marrero, Tania; Marchezini, Victor; Meyreles, Lourdes; Olivato, Débora; Trajber, Rachel; Wisner, Ben
Abstract: Authors discuss school safety and disaster education in Brazil, Colombia, Cuba, the Dominican Republic, Jamaica and Puerto Rico. Case studies explore work to increase understanding of natural hazards and disaster preparedness. Puerto Rico offers innovative examples of reflection on memories of Hurricane Maria by primary students and university undergraduates. From Brazil comes description of work in schools to develop curriculum skills and research competencies at high-school level. The Brazilian scheme encourages schools to become producers of knowledge rather than reproducers of centrally disseminated information. Another case study focuses on efforts to protect university buildings in Colombia. The rich landscape of policy, practice and experience in South America and the Caribbean is informed by a model of the three pillars of Comprehensive School Safety: 1. Safe Learning Facilities, 2. School Disaster Management, and 3. Risk Reduction and Resilience Education.